Straight-Line Trajectory Tracking Control of Unmanned Sailboat Based on NMPC Velocity and Heading Joint Control - Kai Liu; Jiancheng Yu; Wentao Zhao (Journal of Marine Science and Engineering)
This study proposes a trajectory tracking approach for unmanned sailboats that integrates velocity and heading control using nonlinear model predictive control (NMPC). Unlike conventional methods, which typically rely on separate control strategies for maximum velocity and heading, this study employs a joint control framework based on NMPC. This approach allows for constrained control, ensuring that the sailboat operates safely at the desired velocity, forming a foundation for trajectory tracking. The trajectory tracking strategy, built on the joint control of velocity and heading, is further categorized into upwind and non-upwind tracking based on the wind direction. For non-upwind tracking, the desired heading is determined using the Line-of-Sight (LOS) navigation method, while the desired velocity is calculated through a backstepping method grounded in the Lyapunov stability theorem. For upwind tracking, a zigzag strategy is introduced, using the maximum lateral error to switch headings and ensure that the sailboat remains close to the trajectory. The simulation results show that the proposed method can effectively control the velocity and heading and realize accurate trajectory tracking of the unmanned sailboat under different wind conditions. The average error of velocity and heading control is close to zero. During trajectory tracking, the maximum control error is less than 0.35%.